2017
DOI: 10.1038/ncomms16091
|View full text |Cite
|
Sign up to set email alerts
|

Precise inhibitory microcircuit assembly of developmentally related neocortical interneurons in clusters

Abstract: GABA-ergic interneurons provide diverse inhibitions that are essential for the operation of neuronal circuits in the neocortex. However, the mechanisms that control the functional organization of neocortical interneurons remain largely unknown. Here we show that developmental origins influence fine-scale synapse formation and microcircuit assembly of neocortical interneurons. Spatially clustered neocortical interneurons originating from low-titre retrovirus-infected radial glial progenitors in the embryonic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 74 publications
1
24
0
Order By: Relevance
“…An important anatomical dataset from cat cortex showed that PVs are electrically coupled on their dendrites in a distance dependent manner at ~5% to 52% likelihood, and the connections link almost all (56/58 sampled) PVs continuously in a loose syncytium containing highly connected nodes (Fukuda 2017). This supports electrophysiological data arriving at similar estimates of overall electrical connectivity in PVs of ~5% to 62% depending on distance (Gibson and others 1999; Zhang and others 2017), and additionally suggests that the occasional, isolated PV would be outside the electrically connected network (anatomical soloists). This work also tantalizes us with the possibility of hemisphere-wide cooperativity through the continuous gap-junctional syncytium.…”
Section: Regulation Of Cooperativity: Size and Time Scale Of Cooperatsupporting
confidence: 83%
“…An important anatomical dataset from cat cortex showed that PVs are electrically coupled on their dendrites in a distance dependent manner at ~5% to 52% likelihood, and the connections link almost all (56/58 sampled) PVs continuously in a loose syncytium containing highly connected nodes (Fukuda 2017). This supports electrophysiological data arriving at similar estimates of overall electrical connectivity in PVs of ~5% to 62% depending on distance (Gibson and others 1999; Zhang and others 2017), and additionally suggests that the occasional, isolated PV would be outside the electrically connected network (anatomical soloists). This work also tantalizes us with the possibility of hemisphere-wide cooperativity through the continuous gap-junctional syncytium.…”
Section: Regulation Of Cooperativity: Size and Time Scale Of Cooperatsupporting
confidence: 83%
“…While interneurons labeled at the clonal level tend to distribute into local clusters of few neurons 31,32 , findings using barcoded retrovirus libraries for large-scale analyses of specific identified clonal cells show that interneurons disperse broadly in the neocortex 33,34 . A more recent report shows that spatially clustered interneurons from the MGE and ePOA obtained by low-titer retrovirus-injected radial glia in the embryo develop electrical but not chemical synapses after PN14 35 . Although the non-random allocation of interneurons derived from MGE/ePOA seems acknowledged by all authors, restricted clustering of sibling interneurons is still a matter of debate.…”
Section: Discussionmentioning
confidence: 95%
“…Notwithstanding the over‐representation of certain barcodes and ~54% failure rate in barcode recovery, it was concluded that interneuron clones randomly disperse across the forebrain. Further systematic and in‐depth analysis of the original barcoded datasets, however, revealed that spatial clustering is in fact a reliable feature of clonally related interneurons in the forebrain or only the cortex, supporting the contribution of lineage relationship in spatial distribution and organization of interneurons in the forebrain as well as in the cortex …”
Section: Clonal Production and Organizationmentioning
confidence: 90%